Pengaruh Praktik Lean Manufacturing Terhadap Profitabilitas Melalui Minimisasi Persediaan di Industri Elektronik dan Otomotif Indonesia - Wirawana, Hendra; Yunus, Erlinda (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to analyze the impact of lean manufacturing practices on profitability mediated by inventory minimization in the electronics and automotive industries in Indonesia. Given the critical role of lean manufacturing and inventory minimization to increase a company's profitability, a company needs to implement lean manufacturing practices to eliminate waste at the operational level. A low but adequate inventory level will reduce costs borne by the company to contribute to the company's profitability. This research is a replication of Nawanir et al. (2013) study. In the current study, the samples taken were 204 large manufacturing companies that refer to the 2015 Indonesian Standard Business Field Classification (KBLI), with codes KBLI 26 and 29. Company data were obtained from a directory provided by the Data and Information Center of the Ministry of Industry of the Republic of Indonesia (Pusdatin Ministry of Industry). Hypothesis testing using the Partial Least Square technique (smartPLS 3.0 software) shows that lean manufacturing practices implemented as a whole by the company especially in the electronics and automotive industries can minimize inventory and ultimately contribute positively to the company's profitability. Keywords: electronic and automotive industries, inventory minimization, lean manufacturing, profitability